The Role of Stress Induced Martensite in Ductile Metastable Beta Ti-alloys Showing Combined TRIP/TWIP Effects. (2015) - Sun, F.; Zhang, J.Y.; Brozek, C.; Marteleur, M.; Veron, M.; Rauch, E.; Gloriant, T.; Vermaut, P.; Curfs, C.; Jacques, P.J.; Prima, F.
Abstract: A new family of metastable beta type titanium alloys has recently been designed for ductility improvement with large strain-hardening effect. Superior plastic properties were obtained due to collective effects of both phase transformation induced plasticity and twinning induced plasticity. A series of stress induced phase transformations, including stress/strain-induced beta to omega transformation and stress-induced martensitic beta to α" transformations, play particular roles at each deformation stage. The SIM transformations were found to be closely related to the strain-hardening behavior of the material. In this work, the relationship between SIM transformations and strain-hardening effect were studied by microstructural investigations.